2000
DOI: 10.11609/jott.zpj.15.7.295-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of gastro-intestinal parasites in captive birds of Gujarat zoos

Abstract: A total of 106 group faecal samples of different wild birds from Kamal Nehru Zoo, Ahmedabad and Sayyajibaug Zoo, Vadodara, were examined. Out of this 51 (48.11%) were found positive for parasitic infection. Eggs of Ascaris and Capillaria species were observed in 22 (20.75%) and 14 (13.2%) group faecal samples respectively, while the oocyst of Coccidia (Eimeria species) were observed in 19 (17.92%) group faecal samples. Ascardia galli and Cotugnia digonopora were recovered during postmortem of three hariyal pig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 0 publications
2
17
0
1
Order By: Relevance
“…This result was similar to the findings from other surveys in zoos, and this prevalence was higher than among free-ranging birds. The results of Freitas et al (2002) regarding captive psittacids in northeastern Brazil were very similar to ours, thus indicating that the same parasitic agents are associated with Brazilian psittacids all over the country and elsewhere too, since data from studies in other countries also bear similarities to ours (CORDóN et al, 2009;PATEL et al, 2000). Thus, the most important parasites of parrots in captivity are nematodes of the genera Capillaria and Ascaridia.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…This result was similar to the findings from other surveys in zoos, and this prevalence was higher than among free-ranging birds. The results of Freitas et al (2002) regarding captive psittacids in northeastern Brazil were very similar to ours, thus indicating that the same parasitic agents are associated with Brazilian psittacids all over the country and elsewhere too, since data from studies in other countries also bear similarities to ours (CORDóN et al, 2009;PATEL et al, 2000). Thus, the most important parasites of parrots in captivity are nematodes of the genera Capillaria and Ascaridia.…”
Section: Discussionsupporting
confidence: 83%
“…Hemoparasites were also found, namely Plasmodium and Haemoproteus. Patel et al (2000) also found parasite prevalence of 50% among birds at the Gujarat zoo, India, and the most common parasitic genera were Capillaria, Ascaridia and Eimeria.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…The findings of typical capillariid eggs during coprological examinations of psittacine birds kept in captivity are relatively frequent (Landelius et al, 1978;Martı`nez et al, 1999;Patel et al, 2000), but data on the taxonomy and systematics of these nematodes are rare. These relate only to the species Capillaria plagiaticia from Aratinga cactorum (Kuhl) in Brazil and, subsequently, from Nestor notabilis Gould in New Zealand (Wakelin, 1967a).…”
Section: Introductionmentioning
confidence: 99%